Workplace-Oriented English Writing Challenges among Applied English Majors and Teaching Responses - Tian, Haolin; Pan, Lisang; Huang, Xiaoran (International Journal of Social Sciences and Public Administration, 2025)
In vocational undergraduate education, applied English programs place strong emphasis on English writing abilities that can be directly transferred to workplace communication. However, classroom practice indicates that many applied English majors continue to experience difficulties when completing workplace-oriented English writing tasks. Drawing on authentic student writing collected from an English writing course and supplemented by classroom observation, this study examines common challenges in workplace-oriented English writing, with particular attention to task understanding, organizational coherence, and register control. Rather than adopting an experimental intervention, the analysis is grounded in naturally produced classroom texts. The findings suggest that these challenges are closely related to exam-oriented writing habits and limited familiarity with workplace genres. Based on the analysis, practical teaching responses are proposed to support more effective workplace-oriented English writing instruction in applied English programs.